Aristotle's [meteorologica] : meteorology then and now - Tsonis, Anastasios A., (Archaeopress Publishing Ltd., 2020)
Examining the meteorological aspects of Aristotle's work published as "Meteorologica" books A-D, the authors also ask how they compare now with our understanding of meteorology and climate change. In other words, how well did Aristotle fair when he tried to explain weather 2,300 years ago when there was only logic, eye observation, and past experience, with only primitive instrumentation and a few personalized measurements? While there are scientific issues behind Aristotle's writings, this book is written for the non-specialist. The book uses simple examples to present its case, which will be easily followed by general readers.